Pengaruh jenis coolant terhadap efektivitas sistem pendingin mesin mobil avanza tipe 1.3 E MT tahun 2017 - Pohan, Ricki Azhari; Rahman, Jhonni (Jurnal Teknik Mesin Indonesia, 2024)
Technological developments are increasing day by day in the automotive world. The use of vehicles is always accompanied by fuel, where the fuel is used in the combustion process in the cylinder which will cause heat in the engine. The engine temperature must be stabilized with the cooling system to produce optimal engine performance. If the heat does not get good cooling, it will cause changes in the mechanical properties and the shape of the engine components. The nature and components of the machine when it has changed will cause the engine components to be disrupted and reduce the service life of a machine. This study used an experimental method, while the analysis method used a one-factor variation analysis processing by varying the three types of water coolant with rpm variations of 1000, 1500, 2000, and 2300. Measurements were made by measuring the temperature at the inlet and outlet temperatures of the radiator. The variables used in the study these are the heat transfer rate, the overall heat coefficient, and the effectiveness of the fluid.